PEMBERDAYAAN EKONOMI UMAT MELALUI LEMBAGA FILANTROPI ISLAM DI PURWOKERTO - Roli A, Tegar; Anis, Aswhar (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2021)
This study aims to study the pattern of community empowerment carried out by Islamic philanthropic institutions in Purwokerto and to determine the relationship of community empowerment programs that have been implemented by Islamic philanthropic institutions in Purwokerto. This research is a field research (field research) collecting data directly from the field and using a qualitative descriptive approach. While the method of data collection is done by observation, interviews, and documentation. The results showed that the economic empowerment of the people through philanthropic institutions in Purwokerto was carried out in various ways. Empowerment is carried out in two forms, namely empowerment of donors (muzaki) by providing optimal services. The program implementation can run smoothly even though there are human resource constraints in some of the program implementation processes carried out by Islamic philanthropic institutions in this case BAZNASDA and LAZISMU Banyumas.Key Words: Community Economic Empowerment, Islamic Philanthropy Institute, BAZNASDA and LAZISMU Banyumas